The - Heifetz, Ronald A.
Ron Heifetz first defined this problem with his distinctive theory of adaptive leadership in Leadership Without Easy Answers. In a second book, Leadership on the Line, Heifetz and coauthor Marty Linsky highlighted the individual and organizational dangers of leading through deep change in business, politics, and community life. Now, Heifetz, Linsky, and coauthor Alexander Grashow are taking the next step: The Practice of Adaptive Leadership is a hands-on, practical guide containing stories, tools, diagrams, cases, and worksheets to help you develop your skills as an adaptive leader, able to take people outside their comfort zones and assess and address the toughest challenges